Rancang Bangun Sistem Monitoring Jamaah Haji Berbasis Komunikasi Radio - Muhammad Alif Haidar (Politeknik Negeri Malang, 2017)
During the haj pilgrimage, pilgrims getting lost is a problem that often arises. This research created a system that can assist the team leader in monitoring the congregation haji from his entourage. In this system, the team leader and the congregation both have the same equipment using the HC-12 module for radio communication to detect pilgrims leaving the group andArduino Uno and ATmega8 microcontrollers for identification of the congregation. From the results of changing the transmission power and baud rate, the closest measured distance is 1.7 meters and the farthest is 51.1 meters. Each additional power increase of -3 dBm is the same as increasing the power in mW units by 100% and increasing the range by ± 54%. The baud rate of 9600 has a receiver sensitivity of -112 dBm and a baud rate of 2400 has a receiver sensitivity of -117 dBm which increases the distance by ± 54.5%. The less sensitive the receiver can receive the signal strength from a longer range. In the radiation pattern, the team leader device has the widest coverage on the left side or at an angle of 315 degrees to 360 degrees